2015
DOI: 10.1016/j.celrep.2015.08.047
|View full text |Cite
|
Sign up to set email alerts
|

Diminished MTORC1-Dependent JNK Activation Underlies the Neurodevelopmental Defects Associated with Lysosomal Dysfunction

Abstract: SUMMARY We evaluate the mechanisms underlying neurodevelopmental deficits in Drosophila and mouse models of lysosomal storage diseases (LSDs). We find that lysosomes promote the growth of neuromuscular junctions (NMJs) via Rag GTPases and Mechanistic Target of Rapamycin Complex 1 (MTORC1). However, rather than employing S6K/4E-BP1, MTORC1 stimulates NMJ growth via JNK—a determinant of axonal growth in Drosophila and mammals. This role of lysosomal function in regulating JNK phosphorylation is conserved in mamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 70 publications
1
25
0
Order By: Relevance
“…Along similar lines, the observed interaction of FBN1 and TRPML1 is of interest, as FBN1 constitutes a versatile regulator of TGF-β1 signalling (full-length FBN1 sequesters TGF-β1 in microfibrils to prevent TGF signalling, while FBN1 fragments dissociate sequestered TGF-β1 to facilitate TGF signalling) [84]. While it was initially noted that trpml 1 Drosophila larvae show impaired synapse integrity reminiscent of a Drosophila mutant exhibiting impaired TGF-β regulation and synaptic recycling [81,85], the phenotype was later attributed to altered mTORC1/JNK signalling [85]. The possible interplay between TRPML1 activity and TGF-β1 signalling remains unexplored.…”
Section: R-snare Q-snarementioning
confidence: 98%
“…Along similar lines, the observed interaction of FBN1 and TRPML1 is of interest, as FBN1 constitutes a versatile regulator of TGF-β1 signalling (full-length FBN1 sequesters TGF-β1 in microfibrils to prevent TGF signalling, while FBN1 fragments dissociate sequestered TGF-β1 to facilitate TGF signalling) [84]. While it was initially noted that trpml 1 Drosophila larvae show impaired synapse integrity reminiscent of a Drosophila mutant exhibiting impaired TGF-β regulation and synaptic recycling [81,85], the phenotype was later attributed to altered mTORC1/JNK signalling [85]. The possible interplay between TRPML1 activity and TGF-β1 signalling remains unexplored.…”
Section: R-snare Q-snarementioning
confidence: 98%
“…Conversely, in Drosophila models of Batten's disease or mucolipidosis IV, defects in autolysosomal protein degradation pathway lead to synaptic undergrowth by suppressing JNK activation. This study revealed a conserved mechanism by which lysosomal degradation of proteins to free amino acids activates MTORC1 (mechanistic target of rapamycin complex 1), which directly phosphorylates Wallenda to stimulate JNK signaling and promote synaptic growth . Finally, voltage‐gated calcium channels (VGCCs) located on the lysosomal membrane have been identified as novel regulators of autophagic flux.…”
Section: Dynamic Interplay Between Diverse Presynaptic Organelles Orcmentioning
confidence: 99%
“…Recent work has discovered such an activity for the cAMP effector kinase protein kinase A (PKA), which can induce Wnd's activation and function, and is required for its activation in injured axons [42]. Genetic interaction studies have also led to the suggestion that Wnd may also be regulated by TORC1 [43]. It is striking that, as discussed previously, both cAMP and mTOR signaling are known for abilities to unlock axonal regeneration potential.…”
Section: Intrinsic Mechanisms Of Axon Regeneration: Discoveries From mentioning
confidence: 99%